Diet-induced ketosis in adult patients with subacute acquired brain injury: a feasibility study - Edwards, Maria G. P.; Andersen, Jens R.; Curtis, Derek J.; Riberholt, Christian G.; Poulsen, Ingrid (Frontiers in Medicine, 2024)
Research in animal models on cerebral metabolism after brain injury highlights the potential benefits of ketosis in reducing secondary brain injury, but studies in humans are lacking. This study aimed to examine if a six-week ketogenic diet intervention with added medium chain triglycerides was feasible in adult patients with acquired brain injury in the subacute phase, whether ketosis could be achieved and maintained, and to what extent serious adverse reactions, adverse reactions, serious adverse events, and adverse events occur. Patients ≥ 18 years diagnosed with severe acquired brain injury, and an expectation of hospitalization ≥ 6 weeks were included in the intervention group. Excluded patients were included in a standard care reference group. The intervention consisted of a ketogenic diet supplemented with MCT (KD-MCT) to obtain a plasma concentration of β-hydroxybutyrate (BHB) ≥ 0,5 mmol/L. Patients who were enterally fed were given KetoCal ® 2.5:1 LQ MCT Multi Fiber, supplemented with Liquigen ®. Patients consuming oral nutrition were given KetoCal ® 2.5:1 LQ MCT Multi Fiber supplemented with Liquigen ®, in addition to ketogenic meals. During a 13-week inclusion period, 12 of 13 eligible patients (92%; 95% CI: 67% to 99%) were included in the intervention group. Seventeen of 18 excluded patients (94%; 95% CI: 74% to 99%) were included in the reference group. Eight patients (67%) completed the six-week intervention. It took a median of one day to achieve ketosis from starting 100% MCT-KD and it was maintained for 97% of the intervention period after ketosis was obtained. There were no serious adverse reactions to the MCT-KD and patients experienced adverse reactions not considered serious in 9.5% of days with the intervention. The MCT-KD was accepted by patients in all intervention days and in the two patients transitioning from enteral feeding to oral intake, there were no complications related to transitioning. Intervention with MCT-KD is feasible and tolerated for six weeks in hospitalised adult patients with severe brain injury in the subacute phase. Randomised controlled trials are needed to assess benefits and harms of MCT-KD and the effect on patients' recovery.